MAPPING LAND SUITABILITY OF SUBAK ON BASED ON GEOGRAPHYC INFORMATION SYSTEM (GIS) IN DENPASAR, BALI - Trigunasih, Ni Made; Lanya, Indayati; Subadiyasa, I Nengah Netera; Adnyana, I Made (International Journal of Biosciences and Biotechnology, 2016)
This study aims to identify and provide land suitability database of Subak to support sustainable agricultural development and provide spatial information such as land suitability maps with existing inhibiting factor. The method used was field survey to obtain data characteristics/quality of land through soil sampling on several land units sample, and soil analysis in the laboratory. Land suitability classification was done using the criteria from the Technical Instructions Evaluation of Land for Agricultural Commodities by matching between the quality/characteristics of the land with the growing requirements of rice crop being evaluated. The analysis of actual land suitability both of S2 (little suitable) with limiting factors included drainage, texture, depth of planting, salinity, N- available, P-available and K-available, and slope; and S3 (marginally suitable) with limiting factors such as N-available, P-available and salinity. The assumption of business improvements that can be made to the determine quality/characteristics of the land Subak was an inhibiting factor, with optimization by improved drainage channels, N and P in accordance with the needs of the rice plant. Therefore the suitability of potential land for irrigated rice crops can be mapped by GIS and can be increased to very suitable (S1) level. In conclusions, the actual land suitability was categories as 72% little suitable (S2) and 28% marginally suitable or S3 with inhibiting factors included rooting medium, availability of nutrients, slope and salinity. While the suitability of potential land consisted of all of Subak that invery suitable (S1)level, so that the existence of Subak in Denpasar should be protected.
Keywords: Mapping; land suitability; Geographical Information Systems